A response to criticism of the global mental health movement. How polarization can be overcome in theory and in west African social psychiatric practice - Michael Huppertz (Cambridge Prisms: Global Mental Health)
Since the turn of the 21st century, we have seen the development of an international movement that works in various ways to ensure that everyone in the world has access to adequate mental health care. There is indeed a great need for action, especially in countries with weak and underfunded health systems. The Movement for Global Mental Health (MGMH) is supported by strong organizations such as the WHO, academic institutions and NGOs. As this movement has gained momentum, however, it has been accompanied by fierce criticism, in particular from scholars of the humanities and social science, who see the global expansion of psychiatry as a medical discipline as a form of power-grabbing, neocolonialism and capitalist expansion. They also consider psychiatry to be a biologistic discipline, the justification of which they question, in continuation of a long anti-psychiatric tradition. This criticism prompted several adaptations of the MGMH and various efforts towards integration, but these have not been widely accepted by the critics. The following text primarily summarizes, classifies and critically engages with the basic arguments of the aforementioned critique. Theoretical misconceptions regarding the practice of psychiatry are clarified. Subsequently a specific project in Côte d’Ivoire is presented that demonstrates how contextual psychiatry can proceed and how unnecessary dichotomies and polarizations can be overcome in the interests of the persons concerned.